Nutritional characterization and oxidative stability of alpha- Linolenic acid in bread containing roasted ground flaxseed - Marpalle, Pandurang (2015)
Flaxseed (Linum usitatissimum) contain three main bioactive components namely α-linolenic acid, dietary fibers and lignan. These are responsible for numerous reports suggesting positive health benefits from flaxseed. Hence different amounts of ground roasted flaxseed flour was incorporated into bread and soluble and insoluble fibers, in. -vitro protein digestibility, in. -vitro glycemic index (GI), invitro antioxidant activity and α-linolenic acid (ALA) content were evaluated. Protein digestibility of flaxseed enriched bread was significantly lower than the control (70.9 versus 78.5g/100g). In- vitro GI was significantly lower (51.3 compared to 94.6g/100g in the control bread) and ALA content of optimized bread (containing 10g of flaxseed per 100g), as determined using GC-MS, was about 1.51g/100g of bread whereas omega-6 (linoleic acid) content was about 0.15g/100g of bread. During 5 days storage period, peroxide value, anisidine value and free fatty acids were increased in flaxseed supplemented bread samples that were stored at 30°C and at 4°C.